Netrin-1 Promotes M2 Type Activation and Inhibits Pyroptosis of Microglial Cells by Depressing RAC1/Nf-?B Pathway to Alleviate Inflammatory Pain - Yin, Y; Yan, Y; Jin, X; Fu, Y; Chen, Y (Physiological research, 2024)
Netrin-1 (NTN-1) plays a vital role in the progress of nervous system development and inflammatory diseases. However, the role and underlying mechanism of NTN-1 in inflammatory pain (IP) are unclear. BV2 microglia were treated with LPS to mimic the cell status under IP. Adeno-associated virus carrying the NTN-1 gene (AAV-NTN-1) was used to overexpress NTN-1. Complete Freund's Adjuvant (CFA)-induced mouse was recruited as an in vivo model. MTT and commercial kits were utilized to evaluate cell viability and cell death of BV2 cells. The mRNA expressions and secretions of cytokines were measured using the ELISA method. Also, the pyroptosis and activation of BV2 cells were investigated based on western blotting. To verify the role of Rac1/NF-kappaB signaling, isochamaejasmin (ISO) and AAV-Rac1 were presented. The results showed that NTN-1 expression was decreased in LPS-treated BV2 microglia and spinal cord tissues of CFA-injected mice. Overexpressing NTN-1 dramatically reversed cell viability and decreased cell death rate of BV2 microglia under lipopolysaccharide (LPS) stimulation, while the level of pyroptosis was inhibited. Besides, AAV-NTN-1 rescued the activation of microglia and inflammatory injury induced by LPS, decreasing IBA-1 expression, as well as iNOS, IL-1beta and IL-6 secretions. Meanwhile AAV-NTN-1 promoted the anti-inflammation response, including increases in Arg-1, IL-4 and IL-10 levels. In addition, the LPS-induced activation of Rac1/NF-kappaB signaling was depressed by NTN-1 overexpression. The same results were verified in a CFA-induced mouse model. In conclusion, NTN-1 alleviated IP by suppressing pyroptosis and promoting M2 type activation of microglia via inhibiting Rac1/NF-?B signaling, suggesting the protective role of NTN-1 in IP. Keywords: Netrin-1, Inflammatory pain, Pyroptosis, Microglia M2 activation, Rac1/NF-kappaB.
Keywords: Animals; zánět; buněčné linie; lipopolysacharidy; rac1 GTP-Binding Protein; rac1 protein vázající GTP; Mice; pyroptóza; mikroglie; signální transdukce; Lipopolysaccharides; myši; Signal Transduction; Cell Line; netrin-1; Inflammation; bolest; Male; Microglia; Neuropeptides; Netrin-1; Pain; neuropeptidy; Pyroptosis; NF-kappa B; zvířata; mužské pohlaví; Mice, Inbred C57BL; myši inbrední C57BL